Respostas

A melhor resposta!
2014-08-13T20:45:41-03:00
a) f(x)= x² -6x + 5
Δ = b² - 4.a.c
Δ = (-6)² - 4 . 1 . 5
Δ = 36 - 4. 1 . 5
Δ = 16

x = (-b +- √Δ)/2a
x' = (--6 + √16)/2.1      x'' = (--6 - √16)/2.1
x' = 10 / 2                   x'' = 2 / 2
x' = 5                         x'' = 1

b) f(x)= 4x² -4x + 1
Δ = b² - 4.a.c
Δ = (-4)² - 4 . 4 . 1
Δ = 16 - 4. 4 . 1
Δ = 0

x = (-b +- √Δ)/2a
x' = (--4 + √0)/2.4     x'' = (--4 - √0)/2.4
x' = 4 / 8                 x'' = 4 / 8
x' = 0,5                   x'' = 0,5

c) f(x)= x² -4x +5
Δ = b² - 4.a.c
Δ = (-4)² - 4 . 1 . 5
Δ = 16 - 4. 1 . 5
Δ = -4
Delta negativo não existem raízes reais

d) f(x)= -2x +4
-2x=-4   (-1)
2x=4
x=4/2
x=2

e) f(x)= 3x² +6x
x(3x+6)=0
x=0

3x+6=0
3x=-6
x=-6/3
x=-2
1 5 1